May a correlation exist between age and biochemıcal parameters in Covid-19 patients? - Demir, Aslıhan Dilara; Durmaz, Zeynep Hulya (Asian Journal of Medical Sciences, 2021)
Background: Covid-19 infectious disease becomes a pandemic and later affects the entire world it has various effects in different age groups. Aims and Objective: In our study, we aimed to investigate the distribution of biochemical tests along with age, and the incidence in different age groups under the age of 65 and over the age of 65. Materials and Methods: We planned a retrospective study. Our patients consist of 2 groups. The first group consists of 54 patients aged 18 to 65 years, and the second group consists of 38 patients aged 65 years and older. Previously analyzed biochemical parameter values (such as lymphocyte, neutrophil, hemoglobin, platelet, CRP, LDH, AST, ALT, D-dimer, BUN, creatinine) of all patients followed up in our hospital were reached retrospectively through the hospital database. Results: There was a strong negative correlation between Alb and CRP, D-Dimer and albumin, neutrophil and albumin in patients under 65 years of age. A positive correlation was observed between other parameters. Negative moderate correlations were found between albumin and CRP, Potassium and age, WBC and albumin, hemoglobin and creatinine, hemoglobin and LDH, platelets and hemoglobin, lymphocytes and age, lymphocytes and prothrombin time, lymphocytes and D-Dimer, neutrophils and albumin, fibrinogen and creatine kinase, erythrocyte sedimentation rate and AST, erythrocyte sedimentation rate and ALT, erythrocyte sedimentation rate and hemoglobin in patients over 65 years of age. Positive correlations were detected between other parameters. Conclusion: ALT, creatinine, CRP, LDH, D-Dimer, WBC, neutrophil, erythrocyte sedimentation rate was significantly higher in patients over 65 years of age than in patients under 65 years of age. Platelet, lymphocytes were statistically significantly higher in patients under 65 than in patients over 65.